A double-blind randomized controlled trial investigating the effectiveness of topical bupivacaine in reducing distress in children following extractions under general anaesthesia - G. GAZAL, R. BOWMAN, H. V. WORTHINGTON, & I. C. MACKIE (Paediatric Dentistry, 2004)
This study was designed to investigate the effectiveness of topical bupivacaine (0·25%) in reducing postoperative distress following extraction of teeth under general anaesthesia in children.